The Transformative Influence of Artificial Intelligence on Supply Chain Management - Tarihal Balakrishna; Kaliwal Rohit; Ammanagi Ashok (ITM Web of Conferences)
The application of AI in supply chain management has revolutionised how organisations can improve, enhance and even transform their supply chain and operational structures. In the current and future business environment, characterised by globalisation and competition, AI has shifted from being a competitive advantage to a necessity. This paper aims to explore the effects of AI on supply chains with a particular emphasis on how machine learning and other forms of intelligent algorithms can improve decision-making, operational effectiveness and real-time responsiveness. This research focuses on the use of AI technologies like predictive analytics, RPA, and autonomous systems in supply chain management functions like inventory management, demand forecasting, procurement, and distribution. This is because predictive analytics allows organisations to anticipate market and consumer trends, thus improving the organisation’s predictions and planning. RPA involves automating rulebased processes, thus allowing employees to focus on more complex tasks, while autonomous systems, including drones and self-driving vehicles, enhance supply chain management by increasing the speed and reducing A combination of qualitative data collected through interviews and surveys and quantitative data collected through case studies and industry reports was used. The study indicates that AI can significantly decrease lead times, enhance the accuracy of demand planning, and decrease operational costs. However, issues such as scalability, data security, and the issue of employment losses are still crucial issues that need to be discussed. This study also discusses the ethical implications of AI in supply chains, focusing on the workforce impact and providing recommendations for addressing the workforce challenges and enhancing data governance. Through presenting solutions to these challenges, this paper highlights the importance of the ongoing evolution and flexibility of AI-based supply chains. The organisations that are able to tackle these concerns will be in a good place to harness the full value of AI in the supply chain management function.